Role of the crc Gene in Catabolic Repression of the Pseudomonas putida GPo1 Alkane Degradation Pathway - Yuste, Luis (American Society for Microbiology, 2001)
Expression of the alkane degradation pathway encoded in the OCT plasmid of Pseudomonas putida GPo1 is induced in the presence of alkanes by the AlkS regulator, and it is down-regulated by catabolic repression. The catabolic repression effect reduces the expression of the two AlkS-activated promoters of the pathway, named PalkB and PalkS2. The P. putida Crc protein participates in catabolic repression of some metabolic pathways for sugars and nitrogenated compounds. Here, we show that Crc has an important role in the catabolic repression exerted on the P. putida GPo1 alkane degradation pathway when cells grow exponentially in a rich medium. Interestingly, Crc plays little or no role on the catabolic repression exerted by some organic acids in a defined medium, which shows that these two types of catabolic repression can be genetically distinguished. Disruption of the crc gene led to a six- to sevenfold increase in the levels of the mRNAs arising from the AlkS-activated PalkB and PalkS2 promoters in cells growing exponentially in rich medium. This was not due to an increase in the half-lives of these mRNAs. Since AlkS activates the expression of its own gene and seems to be present in limiting amounts, the higher mRNA levels observed in the absence of Crc could arise from an increase in either transcription initiation or in the translation efficiency of the alkS mRNA. Both alternatives would lead to increased AlkS levels and hence to elevated expression of PalkB and PalkS2. High expression of alkS from a heterologous promoter eliminated catabolic repression. Our results indicate that catabolic repression in rich medium is directed to down-regulate the levels of the AlkS activator. Crc would thus modulate, directly or indirectly, the levels of AlkS.